FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN TRANSPORTASI - Mappadang, Agoestina; Ilmi, Syauqi; Handayani, Wuri Septi; Indrabudiman, Amir (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to examine the factors that influence Financial Distress. The research method used is quantitative with secondary data. The population of this research is the transportation companies listed on the Indonesia Stock Exchange in 2013-2017, with a sample of 10 companies and an analysis unit of 50 objects. Multiple Linear Regression is used for hypothesis testing. The results showed that liquidity, leverage, and company size had a positive and significant effect on financial distress, and profitability had a negative and significant effect on financial distress. Whereas Managerial Ownership has no effect on Financial Distress. Keywords: Profitability, Liquidity, Leverage, Company Size, Managerial Ownership, Financial Distress